Melasma Management: A Review of Current Treatment Options - Banstola, Ashmita; Li, Xiao-Lan (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Melasma is a common pigmentary disorder characterized by dark patches on the face, neck, and sternum, most frequently affecting women of reproductive age. Beyond its cosmetic impact, melasma can significantly affect self-esteem and quality of life. Its development involves multiple factors, including genetic predisposition, hormonal influences, ultraviolet radiation, and skin barrier dysfunction. Diagnosis relies on clinical examination, supported by dermoscopy, Wood’s lamp examination, histopathology, and advanced imaging, which also help differentiate it from other pigmentary disorders. Management has evolved considerably, with topical agents and chemical peels remaining first-line options, either alone or in combination. Advances in laser and light-based therapies have expanded treatment choices, while newer modalities such as platelet-rich plasma and microneedling offer less invasive yet effective alternatives. Combination approaches often provide superior outcomes. This review summarizes current knowledge on pathogenesis, diagnostic tools, and therapeutic strategies, aiming to guide clinicians toward effective, individualized, and sustainable management of melasma.